AIMP3 Deletion Induces Acute Radiation Syndrome-like Phenotype in Mice. Issue 1 (December 2018) - Kim, Doyeun; Kim, Sunmi; Oh, Youngsun; Park, Songhwa; Jeon, Yoon; Kim, Hongtae; Lee, Ho; Kim, Sunghoon
Abstract Genomes are mostly protected from constant DNA-damaging threats, either internal or external, which ultimately sustain the organism. Herein, we report that AIMP3, a previously demonstrated tumour suppressor, plays an essential role in maintaining genome integrity in adult mice. Upon induction of the temporal systemic deletion of AIMP3 by tamoxifen in adult mice, the animals developed an acute radiation syndrome-like phenotype, typified by scleroderma, hypotrophy of haematopoietic cells and organs, and intestinal failure. Induction of γH2AX, an early marker of DNA double-strand breaks, was observed in the spleen, intestine, and the highly replicating embryonic cortex. In addition, sub-lethal irradiation of AIMP3 mKO mice dramatically affected organ damage and survival. Using isolated MEFs from conditional KO mice or AIMP3 knockdown cells, we confirmed the presence of spontaneously occurring DNA double-strand breaks by COMET assay and γH2AX induction. Furthermore, γH2AX removal was delayed, and homologous DNA repair activity was significantly reduced. Reduction of RPA foci formation and subsequent Rad51 foci formation probably underlie the significant reduction in homologous recombination activity in the absence of AIMP3. Together, our data demonstrate that AIMP3 plays a role in genome stability through the DNA repair process.